Institutional Bases for The Formation of the Subject of Aviation Infrastructure Management in the System of Ensuring the Sustainability of the Northern Sea Route - T. A. Chernyak (Управленческие науки)
The development of the Northern Sea Route (NSR) infrastructure is one of the priority areas of managerial thought in the development of the Arctic zone of the Russian Federation. Commercial use of high-latitude caravan routes in the waters of the NSR should significantly change the situation with the organization of logistical maritime flows around the Eurasian continent. Ensuring uninterrupted traffic along with fulfilment of the conditions of urgency of delivery and cargo safety form the category of stability of the NSR functioning. Its northern part runs exclusively in domestic seas, and ensuring regular vessel traffic is Russia’s priority task in the competition for transporting cargo from east to west (and back) by sea. The movement of ships along the NSR falls directly under the authority of the management of Rosatom State Corporation, while the management of the infrastructure that ensures the continuous movement of transport along the NSR is carried out collegially. At the same time, such an important aspect as the management of the infrastructure complex supporting the movement of container ships with transit cargo has been assigned to three components of a single management entity: the Ministry of Transport of the Russian Federation, the Ministry of the Russian Federation for the Development of the Russian Far East and the Arctic, and Rosatom Corporation, without clearly defining the boundaries of responsibility for interdepartmental management decisions. To date, this approach has already caused a series of organizational and technical difficulties. The aim of the study is to identify the rational organization of the infrastructure of the management subject, allowing to ensure the sustainability of the movement of passenger and cargo ships throughout the water area of the NSR; it is based on such scientific methods as induction, systematization, grouping Key results of the work may be in demand both in the course of scientific research in the field of infrastructure development in the regions of the Arctic zone of the Russian Federation, and in the framework of improving the existing management system of aviation infrastructure of these territories.